Soxhlet extraction of ascorbic acid from guava - Mohd Firdaus, Mustakim (2009)
Natural antioxidant has gained interest among consumers and the scientific community due to their benefits as inhibitor cardiovascular disease and cancer. In this research, the extraction of antioxidants from guava with soxhlet extraction process has been studied. The effect of drying temperature, solvent polarity, and particle sizes of guava on extraction yields were investigated. Analysis of ascorbic acid content was performed using HPLC. The drying temperatures used were 32°C, 50°C, 60°C and 70°C. The solvents utilized were methanol, ethanol, hexane and pentane. In terms of particle, it was set at 1.0 mm, 3.0 mm, 5.0 mm and 10.0 mm. The results showed that the drying temperature at 50°C gave the highest yield of ascorbic acid which is 38.353mg/l, while using methanol as solvent yield 34.123 mg/l. It indicates that the relation between solvent polarities and yield of ascorbic acid were directly proportional. The particle size of guava was inversely proportional with the extraction yield of ascorbic acid where using 1.0 mm particle size gave 23.546 mg/l amount of ascorbic acid. This study indicated that natural antioxidant from guava has a big potential as an alternative source of antioxidant in order to replace the synthetic antioxidant in current market.